Integrating Research, Theory and Knowledge for Professional Development: A Narrative Inquiry - Pervin, Nasrin (Journal of NELTA Koshi (JoNK), 2024)
This personal narrative in qualitative research investigation delves into the impact of reflection on the personal and professional growth of educators. Critical reflection emerges as a pivotal concept that educators assimilate into their daily practices. Despite ongoing discussions about its essential nature, the role of critically reading and reflecting on theories and research in preparing teachers within South Asian pedagogy remains uncertain. This article adopts a cross-case study approach, incorporating a personal narrative from an educator to explore critical reflection in community development. The researcher critically analyzes two scholarly articles from distinct journals, grounded in the belief that theory and knowledge evolve through simultaneous research and reflection. The study’s findings underscore the importance of reflection in enhancing teachers’ awareness of personal and professional growth, contributing to advanced community knowledge. Improving professional knowledge through research is a key outcome, enabling educators to optimize theory and knowledge for locally relevant, high-quality scholarship.